Cognitive change after electroconvulsive therapy in mood disorders measured with the Montreal Cognitive Assessment. (21st September 2020) - Hebbrecht, K.; Giltay, E.J.; Birkenhäger, T.K.; Sabbe, B.; Verwijk, E.; Obbels, J.; Roelant, E.; Schrijvers, D.; Van Diermen, L.
Abstract : Objective: The Montreal Cognitive Assessment (MoCA) is a sensitive and clinically practical test but its usefulness in measuring long‐term cognitive effects of ECT is unclear. Using the MoCA, we investigated short‐ and long‐term global cognitive change in ECT‐treated patients with a Major Depressive Episode (MDE). Method: We included 65 consecutive ECT‐treated patients with MDE, in whom global cognitive functioning was assessed at baseline (T0); during ECT (before the third session; T1); and 1 week (T2), 3 months (T3), and 6 months (T4) after completion of the index course. Changes in MoCA (sub)scores were analyzed using linear mixed models and reliable change indices were computed to investigate individual changes in MoCA total scores. Results: There was a significant effect of time on MoCA scores ( F (4, 230.5) = 4.14, P  = 0.003), with an improvement in global cognitive functioning from T3 compared to T1 and T2. At the individual level, 26% ( n  = 17) of patients showed a significantly worse cognitive functioning at T2 and 12% ( n  = 8) an improved cognitive functioning compared to T0. For T4, these percentages ameliorated to 8% and 18% respectively. Conclusion: No persistent global cognitive impairment induced by ECT was found at the group level using the MoCA. At the individual level, however, there was clear heterogeneity in the effects of ECT on cognitive functioning. The MoCA is a suitable tool to monitor short‐ and long‐term global cognitive functioning in ECT‐treated patients with MDE but in younger patients, potential ceiling effects must be taken into account.